Identifikasi Faktor Yang Mempengaruhi Kinerja Usaha Mikro Kecil Dan Menengah (UMKM) - Mona Mokodompit; Syarifuddin; Sutiana Mutia (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2019)
This study aims to examine the influence of internal and external factors partially on the performance of Micro, Small and Medium Enterprises (MSMEs) of industrial sector in Manokwari Regency. Research data is obtained by giving questionnaires and interviews to 34 MSMEs owners of industrial sector in Manokwari Regency. The data was then analyzed by using a multiple linear regression analysis tool. The results of this study indicate that internal factors have no significant influence on the performance of MSMEs. Whereas, external factors have a significant influence on the performance of MSMEs.